Alloimmunization in Patients with Sickle Cell Disease in French Guiana. (2nd February 2015) - Elenga, Narcisse; Niel, Loic
Abstract : This study in French Guiana assessed the frequency of alloimmunization to red cell antigens in sickle cell disease patients over 1995–2011 and identified the most common antibodies. A retrospective analysis of the transfusion history and medical records of 302 patients showed that 29/178 transfused patients had developed alloantibodies (16%). The most frequent alloantibodies were anti-LE1, anti-MNS1, anti-LE2, and anti-FY1 and were developed after transfusion of standard red cell units. The frequency of the clinically significant antibodies in this population of SCD patients was 11% (19/178). The antibodies found on those patients who had delayed hemolytic transfusion reaction were anti-K1, anti-FY1, and anti-MNS3. The strategies used to decrease alloimmunization in French Guiana are discussed.